Coolant migration in double-wall effusion cooling systems - van de Noort, M (2023)
Over recent decades, aeroengines have seen continuous rises in Turbine Entry Temperature (TET) as engineers seek to achieve greater values of turbine thermal efficiency. As TETs continue to climb, increasingly sophisticated cooling systems are required to keep component temperatures below their softening levels. This thesis examines the application of one such high performance cooling system: double-wall effusion cooling, which combines impingement, pedestal, and effusion cooling. A particular focus is placed on the effects of coolant migration, where coolant in the pedestal cavity moves under the influence of an external pressure gradient, potentially producing a dangerous maldistribution of outlet coolant flow which could lead to hot gas ingestion.